Sintesis Silika Alam dari Kalsinasi Sekam Padi - Rahmi, Rahmi (Lembaga Yasin AlSys, 2024)
Indonesia is an agricultural country, where 40% of the livelihood of the majority of the population is farming. The factor that makes Indonesia an agricultural country is that apart from its population working in the agricultural sector, Indonesia is also crossed by fertile mountain ranges. In an agricultural country like Indonesia, agriculture makes an important contribution to the economy and fulfills people's basic needs. The increase in population will be proportional to the increase in the number of basic needs available. Survey results from the National Statistics Agency show that in 2022 Indonesia will experience an increase in rice production of 1.25 million tons from the previous year. Along with the increase in agricultural production, a new problem that arises is the large number of agricultural residues that are not used optimally, for example, such as rice husks. On average, every 1 kilogram of rice produced can produce 0.28 kg of rice husks. Rice husks contain a high silica content. Based on research that has been carried out, it was found that the silica content was 98-99.9% silica using the sol gel method.